2015
DOI: 10.1093/hmg/ddv357
|View full text |Cite
|
Sign up to set email alerts
|

CDC174, a novel component of the exon junction complex whose mutation underlies a syndrome of hypotonia and psychomotor developmental delay

Abstract: Siblings of non-consanguineous Jewish-Ethiopian ancestry presented with congenital axial hypotonia, weakness of the abducens nerve, psychomotor developmental delay with brain ventriculomegaly, variable thinning of corpus callosum and cardiac septal defects. Homozygosity mapping identified a single disease-associated locus of 3.5 Mb on chromosome 3. Studies of a Bedouin consanguineous kindred affected with a similar recessive phenotype identified a single disease-associated 18 Mb homozygosity locus encompassing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It was reported that the MTMR2 and MTMR5 genes are highly expressed in the testicles, especially in germ cells and in Sertoli, and the deactivation of any of these genes produces spermatogenic defects [83]. CCDC174 (coiled-coil domain-containing 174) is essential for neuronal differentiation; in human, mutations affect psychomotor developmental delay and abducens nerve palsy [85]. The CCDC174 gene is not yet reported in reproductive processes; however, other members of this family are associated with these processes.…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…It was reported that the MTMR2 and MTMR5 genes are highly expressed in the testicles, especially in germ cells and in Sertoli, and the deactivation of any of these genes produces spermatogenic defects [83]. CCDC174 (coiled-coil domain-containing 174) is essential for neuronal differentiation; in human, mutations affect psychomotor developmental delay and abducens nerve palsy [85]. The CCDC174 gene is not yet reported in reproductive processes; however, other members of this family are associated with these processes.…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…There is limited information regarding C3ORF19. Also known as coiled-coil domaincontaining 174 or CCDC174, C3ORF19 co-localizes with the ATP-dependent helicase Eif4a3, a component of the exon junction complex (16,17). The sub-cellular localization of C3ORF19 is restricted to the nucleus (16).…”
Section: Discussionmentioning
confidence: 99%
“…These data strongly suggest that eIF4A3 plays an important role in the heart, including contractility and sarcomerogenesis. Mutation in another EJC component CDC174 results in loss of skeletal muscle myofibrils, suggest a strong link between EJC activity and striated muscle structure [31].…”
Section: Discussionmentioning
confidence: 99%